Immigration and Identity in the Middle Ages : French Immigrants to Constantinople and Greece in the Thirteenth Century - Gilles, Erica Jo (Centre d'études médiévales Saint-Germain d'Auxerre, 2006)
After capturing Constantinople in 1204, the Fourth Crusaders established several states in former Byzantine territory. Starting from the captured imperial center, westerners moved into Thrace, Greece, the Aegean islands, and even Asia Minor. These campaigns of conquest had varied success, with the greatest and longest lasting in southern Greece . The Fourth Crusaders had struck out for the east as warriors, not as immigrants, and after a year, many of them returned to their homelands. Some remained,...